High Levels of Adhesion Molecules Are Associated with Impaired Endothelium-dependent Vasodilation in Patients with Peripheral Arterial Disease - Brevetti, Gregorio; Martone, Vincenzo D.; de Cristofaro, Tiziana; Corrado, Salvatore; Silvestro, Antonio; Di Donato, Anna Maria; Bucur, Roxana; Scopacasa, Francesco (Thrombosis and Haemostasis, 2001)
Soluble intercellular adhesion molecule-1 (sICAM-1) and vascular cellular adhesion molecule-1 (sVCAM-1) were measured alongside flow-mediated vasodilation (FMD) in 34 patients with intermittent claudication and 14 control subjects. Patients with plasma sICAM-1 >253 ng/mL (median value) showed lower FMD than those with sICAM-1 <253 ng/mL (5.6 ± 1.8% vs 9.6 ± 4.2%, p <0.01). Similarly, in the 17 patients with plasma sVCAM-1 >414 ng/mL, FMD was lower than in the remaining 17 patients (6.1 ± 1.9% vs 9.2 ± 4.5%, p <0.05). Additionally, when endothelial dysfunction was defined as FMD ≤5.5%, patients with FMD below this value had higher plasma concentrations of sICAM-1 and sVCAM-1 than those with FMD >5.5%. Therefore, our findings indicate a close association between elevated plasma levels of adhesion molecules and endothelial dysfunction. As impaired endothelial function is one of the first steps in atherogenesis, our findings have clinical relevance since they serve as the basis for further evaluation of sICAM-1 and sVCAM-1 as potential plasma markers for progression of atherosclerosis in a population at high risk.
Keywords: Adhesion molecules; flow-mediated dilation; endothelial dysfunction; intermittent claudication; peripheral arterial disease